A Blueprint for Improving the Promotion and Delivery of Adult Vaccination in the United States - Harris, Katherine M. (RAND Corporation, 2012)
Vaccine-preventable disease continues to take a heavy toll on adults despite the widespread availability of effective vaccines. This report identifies where efforts to improve the delivery of adult vaccination have stalled and recommends targeted strategies that are supported by available evidence and build on existing infrastructure.